2004
DOI: 10.1186/1477-7827-2-78
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Recently, several members of the transforming growth factor-beta (TGF-beta) superfamily have been shown to be essential for regulating the growth and differentiation of ovarian follicles and thus fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…The intra-and inter-assay coefficients of variation (CV) for three standard sample assayed at approximately 20, 50 or 80% binding both averaged !20% and no samples were below the sensitivity of the assay. At the end of culture, following collection of the media, unattached cells were removed by washing, and attached cells were lysed using incubation at 37 8C in distilled water for 1-2 h. Cell lysates were frozen at K70 8C until assayed for DNA content using a Hoechst 33258 based dye assay (Juengel et al 2004). Intra-and inter-assay CV were !10%, and no samples were below the sensitivity of the assay.…”
Section: Culture Of Luteinising Ovine Granulosa Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intra-and inter-assay coefficients of variation (CV) for three standard sample assayed at approximately 20, 50 or 80% binding both averaged !20% and no samples were below the sensitivity of the assay. At the end of culture, following collection of the media, unattached cells were removed by washing, and attached cells were lysed using incubation at 37 8C in distilled water for 1-2 h. Cell lysates were frozen at K70 8C until assayed for DNA content using a Hoechst 33258 based dye assay (Juengel et al 2004). Intra-and inter-assay CV were !10%, and no samples were below the sensitivity of the assay.…”
Section: Culture Of Luteinising Ovine Granulosa Cellsmentioning
confidence: 99%
“…Collection and culture of ovine granulosa cells were as previously described (Juengel et al 2004). Briefly, ovaries were collected from the local abattoir and transported back to the laboratory.…”
Section: Culture Of Luteinising Ovine Granulosa Cellsmentioning
confidence: 99%
“…TGFB1 has also been detected in oocytes of goat preantral follicles (Rodrigues et al, 2014). TGFB1 and 2 both reduced numbers of granulosa cells after culture in sheep (Juengel et al, 2004a), although no effect of TGFB1 on proliferation was observed (TGFB2 was not tested). In cattle, the effects of TGFB are inconsistent, with TGFB2 having a mild stimulatory effect on proliferation (Gilchrist et al, 2003), and TGFB (type unspecified) having no effect on unstimulated, or an inhibitory effect on epidermal growth factor (EGF)-stimulated, proliferation (Skinner et al, 1987).…”
Section: Introductionmentioning
confidence: 98%
“…In sheep, TGFB1 and TGFB2, but not TGFB3, are produced by ovarian follicles, in the theca cells of type 3 and larger follicles (Juengel et al, 2004a). In cattle, TGFB1, 2 and 3 were all detected in oocytes, granulosa and theca cells, with TGFB3 being the most strongly expressed (Nilsson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation